(untitled) (GEOmedia, 2010)
Avalanche risk management and XML applications The most powerful tool for early warning and mitigating the risk of an avalanche has arisen in the last few years. A standard application model has been already accepted at Open Geospatial Consortium. When CAAML, as model for structured electronic exchange of avalanche related information, will become also standard at European community, public avalanche bulletins and professional network observations could be shared at regional and national level among organizations promoting safety services and avalanche awareness such as AINEVA and METEOMONT. This system will create a common platform for professional and public information exchanges that will open doors to a wide array of opportunities for data sharing, viewing and analyzing based on WFS/WMS services.